Alveolar Socket Sealing Using Mucosal Grafts for Alveolar Ridge Preservation - Nurul Ain Binti Mohamed Yusof; Rusmizan bin Yahaya; Yuhaniz bt Ahmad Yaziz (Cakradonya Dental Journal)
The fresh extraction socket in the alveolar ridge poses a significant challenge in clinical practice, requiring the preservation of both the hard and soft tissue envelope to maintain stable ridge volume. Alveolar Ridge Preservation (ARP) is a surgical procedure aimed at minimizing bone loss following tooth extraction. It helps reduce the need for more complex treatments and optimizes outcomes for future prosthetic replacements of missing teeth. Various ARP techniques have been developed, including Guided Bone Regeneration (GBR), socket fillers, and socket sealing. Alveolar Socket Sealing (ASS) is a procedure that utilizes mucosal grafts or biomaterials to seal the socket, either to complement GBR or function independently to preserve soft tissue and prevent tissue collapse. This report presents two cases using the ASS procedure with mucosal grafts, a free autogenous tissue graft (FGG) and a Platelet-Rich Fibrin (PRF) membrane to seal the alveolar extraction sockets. These techniques were combined with the placement of xenograft bone grafting material. Both clinical approaches successfully limit bone dimensional changes while providing a cost-effective treatment strategy for dental implant placement.